Water, Energy and Food Supply Security in the Gulf Cooperation Council (GCC) Countries—A Risk Perspective - Mohammad Al-Saidi (5751827) (2019)
Supply systems for water, energy and food in the Gulf region are becoming highly interlinked. In the last decades, interdependence was evident in the increase of coproduction plants and the cross-sectoral resource use footprints. In light of increasing integration due to growing scarcities, the construction of mega projects for coproduction, and the use of renewables across sectors, the security notion can be revisited. This paper proposes a view of the resource supply security based on the systems’ characteristics under change and their ability to deal with risks and shocks (resilience). It introduces internal and external risk factors for the water, energy and food supply systems in the Gulf region and highlights recent knowledge on such risks. Further, the paper explains the vulnerability of supply systems to planning risks like scale, integration intensity and level of service provisions together with risks related to growth, technology, market and climate. In light of such insecurities, we stress the importance of investing in risk management and resilience policies in infrastructure planning. Response measures to future risks can focus on options like storage, knowledge, diversification and, importantly, promoting regional cooperation and synergies from common infrastructure planning between countries of the Gulf Cooperation Council (GCC). Other Information Published in: Water License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/w11030455